2003
DOI: 10.1002/pola.10738
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization, and biological activity of N‐(4‐acetylphenyl)maleimide and its oxime, carbazone, thiosemicarbazone derivatives and their polymers

Abstract: A new type of maleimide monomer, N-(4-acetylphenyl)maleimide (NAPMI), was synthesized. The oxime, carbazone, and thiosemicarbazone derivatives of NAPMI were prepared with hydroxylamine hydrochloride, semicarbazide hydrochloride, and thiosemicarbazide hydrochloride, respectively. Radical homopolymerization of NAPMI and its derivatives were prepared at 60°C in dimethyl sulfoxide solution with azobisisobutyronitrile as an initiator. The monomers and theirs homopolymers were characterized with Fourier transform in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 43 publications
0
16
0
Order By: Relevance
“…moiety as pendent group to a polymer backbone has been attempted to get some uses by free radical polymerization or macromolecular reactions. [14][15][16][17] Poly(N-isopropylacrylamide) (PNIPAAm) is one of the well-known thermo-responsive polymers. It exhibits a lower critical solution temperature (LCST) in aqueous media, below which the polymers are water-soluble and above which they become significantly less water-soluble or water-insoluble.…”
Section: Introductionmentioning
confidence: 99%
“…moiety as pendent group to a polymer backbone has been attempted to get some uses by free radical polymerization or macromolecular reactions. [14][15][16][17] Poly(N-isopropylacrylamide) (PNIPAAm) is one of the well-known thermo-responsive polymers. It exhibits a lower critical solution temperature (LCST) in aqueous media, below which the polymers are water-soluble and above which they become significantly less water-soluble or water-insoluble.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that the peak was quite specific spectral data [59][60][61][62]. The 13 C-NMR signal of CH=N function of azomethylene and C=C function of compounds 3a-h appeared at 133-147 ppm and 133-135 ppm, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The oxime, carbazone, and thiosemicarbazone derivatives of N (4-acetylphenyl) maleimide were radical homopolymerized and the polymer obtained shows good antimicrobial activity [24]. Patel et al [25] prepared furan resins derived from o-cresol and furfural under various reaction conditions by a polycondensation technique.…”
Section: Introductionmentioning
confidence: 99%